Ernesto Cardenal: A Latin American Liberation Mystic - Marcela Raggio (Religions, 2023)
This paper explores mysticism as seen in Ernesto Cardenal’s El Evangelio en Solentiname (The Gospel in Solentiname), aiming at both defining Cardenal as a revolutionary and a traditional mystic, shaped by Thomas Merton’s influence and by Latin American political circumstances. Mysticism is usually defined as individual contemplation of God, immediate and unmediated. Yet, in the context of Latin American 20th-century struggles for liberation, mysticism became contemplation of God while the individual is committed to the community. This perspective is studied in Cardenal’s book, supported with his memoir Las ínsulas extrañanas (The Strange Islands), to show that Cardenal is a mystic, notwithstanding his political commitment, or precisely because of that. The theoretical background draws notions from liberation theology and liberation philosophy. Paradoxically, in spite of its revolutionary claims, Cardenal’s The Gospel in Solentiname can be seen in the line of traditional mysticism, in its challenge of power from the margins and its presentation of alternative modes of communicating with the divine.